Investing in medication adherence improves health outcomes and health system efficiency Adherence to medicines for diabetes, hypertension, and hyperlipidaemia - Khan, Rabia (OECD Publishing, 2018)
Poor adherence to medications affects approximately half of the patient population, leading to severe health complications, premature deaths, and an increased use of healthcare services. The three most prevalent chronic conditions - diabetes, hypertension, and hyperlipidaemia - stand out regarding the magnitude of avoidable health complications, mortality, and healthcare costs. There are three broad reasons behind these low rates of adherence to chronic disease medications. Firstly,the problem of poor adherence has rarely been explicitly included in national health policy agendas. Secondly, interventions tend to attribute the problem exclusively to patients, while the evidence suggests that health system characteristics - in particular the quality of patient-provider interaction, procedures for refilling prescriptions, or out-of-pocket costs - are lead drivers. Thirdly, patients with chronic conditions frequently feel left out of the decision about their therapy and are inclined to rebuff. This paper identifies enablers that are needed for improving adherence to medication at the system level
Keywords: Social Issues/Migration/Health